Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1192/bjo.2020.103
|View full text |Cite
|
Sign up to set email alerts
|

Problem severity and waiting times for young people accessing mental health services

Abstract: Background Access to timely care is a quality standard underpinning many international healthcare models, and long waiting times for child and adolescent mental health services are often reported as a barrier to help-seeking. Aims The aim of this study was to examine whether young people with more severe problems have shorter waiting times for mental health services. Method Multilevel multinomial regression analysis controlling for service-area deprivation, age, gender,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Furthermore, in our sample waiting time appeared to be a problem. This is in accordance with previous research [ 62 , 63 ] and indicates that the number of young adults in need of treatment exceeds the available treatment resources. This problem needs particular attention from policy makers and governments, and suggests that rearrangement of treatment resources for youngsters might be necessary.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, in our sample waiting time appeared to be a problem. This is in accordance with previous research [ 62 , 63 ] and indicates that the number of young adults in need of treatment exceeds the available treatment resources. This problem needs particular attention from policy makers and governments, and suggests that rearrangement of treatment resources for youngsters might be necessary.…”
Section: Discussionsupporting
confidence: 93%
“…the GP or school contact person) to help assess their symptoms and the need for treatment. Previous research has found promising effects from education and awareness programmes on mental health literacy, help-seeking behaviour or intention to seek help and stigma reduction [59][60][61][62][63], using different methods including psycho-education and (video) presentations with former patients.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Importantly, however, many more young people are suggested to experience adverse symptoms and effects of mental health conditions without meeting the threshold for clinical diagnosis [ 9 ]. More recent crises, most notably the COVID-19 pandemic, have intersected with ongoing system-wide challenges (e.g., deficits in specialist young people’s mental health provision [ 10 ]), and exacerbated health and wellbeing issues for many young people [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, of those young people and families who are referred to CAMHS, one in four were not accepted into treatment [2]. Demand outstrips supply to such an extent that some CAMHS services set their acceptance thresholds based on imminent risk to self or others, leaving many young people with treatable mental health conditions unable to access CAMHS or facing extra-ordinary waiting times [3].…”
Section: Introductionmentioning
confidence: 99%